Impacts of empty fruit bunch applications on soil organic carbon in an industrial oil palm plantation. (1st September 2022) - Noirot, Lauriane Marie; Müller-Stöver, Dorette Sophie; Wahyuningsih, Resti; Sørensen, Helle; Sudarno,; Simamora, Abedgeno; Pujianto,; Suhardi,; Caliman, Jean-Pierre
Abstract: Extensive oil palm plantations have often resulted in the decrease of soil organic carbon (SOC). Several options exist to counter this, such as recycling empty fruit bunches (EFB) as a soil amendment. However, the extent to which EFB increase SOC has been disputed. Since EFB could also be used as a climate change mitigation tool, it is necessary to truly understand their impact on SOC. The investigation of the impact of nine EFB treatments (differing in frequency and application rates) on a 27-year-old large-scale experiment (Lampung, Sumatra, Indonesia) revealed that, while EFB impacts are heterogeneous throughout the plantation, they can positively affect total SOC and permanganate oxidisable carbon (POX-C) both at shallow and deep depths (measured up to 100 cm). POX-C was closely correlated to SOC, but showed significant increases compared to the untreated control in all treatments, while total SOC was only increased in a few treatments with small and frequent rates of EFB application. Overall, between 12 (±16) and 56 (±12) t ha − 1 of carbon were sequestered under the harvesting path after 21 years. Focussing on the mineral nutrition value of the EFB, oil palm companies apply a rate of 60 t of EFB every second year for their commercial production, and the analysis of three commercial plots showed that the commercial rate only increased POX-C while it had no effect on the total SOC and SOC stocks. It seems obvious that a change of paradigm is necessary to consider EFB recycling as a new management perspective, where the potential for carbon sequestration becomes an important variable for climate change mitigation besides the initial objective of integrating EFB application into the fertiliser management plan of a plantation. Highlights: The frequent application of small rates of EFB increased soil carbon stocks. High application rates did not lead to the highest amount of carbon sequestered. Management of EFB recycling should be reconsidered in a climate mitigation perspective.